Hispanic Organizational Interest in Language Maintenance - Sole, Yolanda R. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
The purpose of this study, which is based on a survey of 116 Hispanic organizations in the United States, is threefold: (1) to explore the organizational background characteristics that might distinguish linguistically retentive from non-retentive organizations; (2) to determine whether there is any differential/ non-differential interest in language maintenance among diverse Hispanic groups; and (3) to ascertain whether language attitudes towards Spanish are differentially/ non-differentially defined at Mexican American, Puerto Ricans and Hispanic organizations at large. The data on all pertinent variables were gathered through mail questionnaires during the summer of 1976. Organizational background characteristics reflect distinctive settlement patterns and density of Hispanic sub-groups in this country. While the nativity status and age groups of the general membership of these organizations does not differ significantly by ethnic sub-group, the core membership does. Three fourth of the organizations surveyed claim as their main concerns the improvement of socioeconomic conditions and/or furthering of educational attainment among fellow ethnics, and one fourth also claim active concern for the preservation of their ethnic heritage. While nearly all associations espouse language maintenance, they differ in the justifications they advance in its favor. The behavioral manifestations of commitment to language maintenance are less pervasive than positive attitudes towards Spanish. (Author/CLK)
ERIC Note: Paper presented at the Southwest Areal Language and Linguistics Workshop (6th, Long Beach, California, April 15, 1977).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bilingualism; Demography; Ethnic Distribution; Ethnic Groups; Ethnicity; Language Attitudes; Language Maintenance; Language Research; Language Usage; Mexican Americans; Minority Groups; Organizations (Groups); Puerto Ricans; Sociolinguistics; Spanish; Spanish Americans; Spanish Speaking; Surveys; Speeches/Meeting Papers